Peer Group Support Meningkatkan Kepatuhan Pengobatan Pada Pasien Tuberkulosis Paru Di Wilayah Kerja Puskesmas Klampis Bangkalan - Lailatun Ni’mah; Uswatun Hasanah; Makhfudli Makhfudli (Fakultas Ilmu Kesehatan, 2018)
Lung tuberculosis is the most concern disease in the world now. In 2014, about 1,2 million people died by tuberculosis. Klampis district on January until March 2017 had 41 klien of lung tuberculosis, and 1 person has recurrence. The data presented that some of klien had disobedient in treatment. The purpose of this study was to increase the obedience of lung tuberculosis treatment in Klampis district Bangkalan. Design this study was Quasy Experiment with pre test and post test group. The sample of this study was 36 people with purposive sampling technics. The independent variable of this study was peer group support, and the dependent variable of this study was the obedience of lung tuberculosis treatment. The data in this study collection analyzed with chi square statistical test and Mc Nemar test. The result of this study with chi square statistical showed that the obedient of lung tuberculosis treatment had significant association (p=0,005) and the result of Mc Nemar test showed that the obedience of taking tb drug no mush significant change to the order obedience variable (p=0,004). The results of this study are peer group support has an influence on the level of adherence when taking medication and how to take medicine in pulmonary tuberculosis clients. It can be concluded that peer group support can be used as an additional intervention to improve medication adherence to pulmonary tuberculosis clients.